Experimental Study on Failure Mechanism of Advanced High Strength Steels in Air Bending Process - N Pornputsiri; K Kanlayasiri (My University, 2018)
This research investigated the failure phenomena and underlying damage mechanisms in small curvature bending and spring-back angles of two advanced high strength steel (AHSS) sheets (TRIP780 and DP980). The study also examined the effect of the bending angle on the failure mechanism. In the analysis, this research utilized an optimal microscope (OM), scanning electron microscope (SEM) and energy-dispersive X-ray spectroscope (EDX). The research findings indicated that the bending force and the bending angle were positively correlated and that the spring-back and bending angles were inversely correlated. On the failure mechanism, at the 45° bending angle, the initial crack was identified on the outer region of the LD-rolling DP980 sheet, while no visible crack emerged for the TD-rolling TRIP780 until arriving at the 60° bending angle, indicating that, by comparison, the former possessed the lowest bendability and the latter the highest.
Keywords: Failure mechanism; Metal Forming Simulation Techniques